Nontyphoidal salmonellosis, transmission through the consumption of contaminated food of poultry origin. (Colombia Medica, 2006)
Salmonella spp. infection is one of the most important causes of gastroenteritis in human beings. The principal reservoirs of these microorganisms are carrying asymptomatic animals and the sources of more frequent infection are the food or the products derived from these. The increase of the incidence of Salmonella is of great impact in public health and animal health and it has been related to an increase of the dissemination of the microorganisms across the productive animal chains (bovine, pigs, broilers and especially layers hens). The present paper has been designed to realize a systematical compilation of information referred to the gastroenteritis and others infections produced for nontyphoidal strains of Salmonella spp. with emphases on the importance of the food of poultry origin in its transmission. The microorganisms frequently can infect the poultry; the eggs can be contaminated for vertical transmission, during the lay, manipulation or storage. The infection in human beings is acquired by consumption of chicken, either raw or partially cooked egg, or food prepared with these. Nontyphoidal salmonellosis (gastroenteritis) can include diarrhea, headache, abdominal pain, nausea, vomiting, fever and dehydration especially in children and elders. Nontyphoidal strains of Salmonella spp. can cause bacteremia, carrying state or infections like meningitis, arthritis, septic arthritis, osteomyelitis, cholangitis, pneumonia, arteritis, endocarditis or urinary tract infections.